2008
DOI: 10.1021/pr700835y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Hippocampal Protein Expression at 3 Days, 3 Weeks, and 3 Months Following Induction of Perinatal Asphyxia in the Rat

Abstract: Perinatal asphyxia (PA) was induced in Sprague-Dawley rats; pups were sacrificed 3 days, 3 weeks, and 3 months following the asphyctic insult, and hippocampal protein levels were determined by a gel-based proteomic method. Levels of antioxidant, metabolic, cytoskeleton, signaling, channel, proteasomal, chaperone, splicing, and synaptosomal proteins were dysregulated depending on the age following induction of PA. These proteins are proposed to be potential markers or pharmacological targets for PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 84 publications
(156 reference statements)
0
18
0
Order By: Relevance
“…Concomitantly, the same functional groups have been reported as resulting from research projects dedicated to the translational alterations identified by differential protein profiling [39]. These extensive alterations in the central molecular pathways can be potentially implicated in the development of potential asphyxia-related chronic complications, such as several sorts of degenerative processes in organs and onset of pre/cancerous lesions in the affected organs as summarised in Fig.…”
Section: Expression Profiling By “Gene Hunting”- Technology Discoverementioning
confidence: 82%
“…Concomitantly, the same functional groups have been reported as resulting from research projects dedicated to the translational alterations identified by differential protein profiling [39]. These extensive alterations in the central molecular pathways can be potentially implicated in the development of potential asphyxia-related chronic complications, such as several sorts of degenerative processes in organs and onset of pre/cancerous lesions in the affected organs as summarised in Fig.…”
Section: Expression Profiling By “Gene Hunting”- Technology Discoverementioning
confidence: 82%
“…Protein extracts prepared were subjected to 2-DE as described elsewhere and 800 lg of protein were applied (Weitzdorfer et al, 2008).…”
Section: Two-dimensional Gel Electrophoresismentioning
confidence: 99%
“…The consumption of extra energy for the reestablishment of homeostasis might compete with the demands required for circuitries and synapsis consolidation [55]. Several studies using the Swedish experimental model have reported distinct alterations induced by PA such as thickening of both pre- [32] and postsynaptic densities [2429, 50]; protein misfolding, aggregation, and ubiquitination [2429]; interruption of postnatal neurogenesis [58]; reduction in neurite length and branching [59, 60]; myelination deficits [63]; and modifications in the levels of synapsin [52, 60] and neurotrophic factors [61]. Some researchers have suggested the existence of plastic changes in an attempt to counterbalance neuronal loss [29, 32, 52, 57].…”
Section: Discussionmentioning
confidence: 99%
“…An Austrian group was also interested in protein derangements during postnatal development following PA and attempted to identify differentially expressed proteins that might represent potential biomarkers and pharmacological targets [52]. They decided to study hippocampal proteins following their own report of postnatal changes during brain development [53].…”
Section: Effects Of Experimental Perinatal Asphyxia On Synaptic Ormentioning
confidence: 99%
See 1 more Smart Citation